RETENSI HARA BEBERAPA BIOCHAR DARI LIMBAH TANAMAN DAN PENGARUHNYA TERHADAP SERAPAN N,P, K TANAMAN PAGI GOGO. - Sukartono Sukartono (Department of Agronomy Faculty of Agriculture University of Mataram and Indonesian Society of Agronomy Branch NTB, 2019)
ABSTRACT Application of biochar to agriculture soils has been considered as means to improve soil quality and carbon sequiestration. Therefore, the understanding of chemical and physical properties of biochars is important to identify suitable use of biochar for improving soil fertility and carbon sequestration. Biochars were produced from phyrolizing five different feedstock from crops residues (rice straw- BPJ, rice husk- BPS, maize cobs- BJT, peanuts shell- BKC and soybean residues-BKE). Using muffle furnace heating under 400oC. The potential nutrients retention of those biochars in particular for NH4+, K+. Ca++, dan Mg++. was tested. througha leaching experiment established in Soil Physic laboratory at Faculty of Agriculure, University of Mataram . The physicochemical properties of biochars were likely varied among fives feedstocks. The biochars derived from soybean residues (BKE), peanut biomass (BKC) and maize cobs (BJT) contained higher mutrients (i.e. C, N, K, Ca and Mg) compared to biochars produced from rice straw (BJP) and rice husks (BPS). Total-C of BKE, BKC dan BJT were 51,73; 57,36 dan 53,53 % respecively. The variation of phyisicochemical properties from different biomass strongly related to different nutrient retention whenever the biochars are applied in soils. Biochars produced from legume crops biomass such as soybean and dan peanuts werethe highest nutrients retention, followed by maize cobsand rice straw biochars. Unde glass house test, the tree biochars namely BPS, BJT and BKE have similar effect on N,P, K uptake as well as to dry weight biomass.